Effects of a Web-Based Autonomy-Supportive Intervention on Physical Education Teacher Outcomes - Henri Tilga; Hanna Kalajas-Tilga; Vello Hein; Lennart Raudsepp; Andre Koka (MDPI AG, 2021)
The current study tested the efficacy of a web-based autonomy-supportive intervention program on changes in physical education (PE) teachers' self-reports of autonomy support, psychological need satisfaction, intrinsic motivation, and teaching efficacy for students' engagement. In this study, 101 secondary school PE teachers and their 652 students were randomized either to a web-based autonomy-supportive experimental group or to the control group. Manipulation checks indicated that the intervention was effective as students perceived the experimental group PE teachers as more autonomy-supportive and less controlling compared to the control group at the one-month follow-up. In the main analysis, results of the path analysis demonstrated direct effects of the intervention on changes in teachers' self-reported autonomy-supportive behaviour, and on teaching efficacy for students' engagement. There were also significant direct effects from changes in autonomy-supportive behaviour on changes in psychological need satisfactions, from psychological need satisfaction on intrinsic motivation, and from intrinsic motivation on teaching efficacy for students' engagement. Finally, the intervention had an indirect effect on changes in teaching efficacy for students' engagement via changes in teachers' autonomy-supportive behaviour, psychological need satisfaction, and intrinsic motivation. These findings provided insight on the effects of a web-based autonomy-supportive intervention for PE teachers on several teachers' outcomes in the context of PE.